Two new and potentially highly threatened Megophrys Horned frogs (Amphibia: Megophryidae) from Indochina’s highest mountains - Tapley, Benjamin; Cutajar, Timothy; Mahony, Stephen; Nguyen, Chung Thanh; Dau, Vinh Quang; Luong, Anh Mai; Le, Dzung Trung; Nguyen, Tao Thien; Nguyen, Truong Quang; Portway, Christopher; Luong, Hao Van; Rowley, Jodi J. L. (Zootaxa, 2018)
Megophrys are a group of morphologically conserved, primarily forest-dependent frogs known to harbour cryptic species diversity. In this study, we examined populations of small-sized Megophrys from mid- and high elevation locations in the Hoang Lien Range, northern Vietnam. On the basis of morphological, molecular and bioacoustic data, individuals of these populations differed from all species of Megophrys known from mainland Southeast Asia north of the Isthmus of Kra and from neighbouring provinces in China. Further, the newly collected specimens formed two distinct species-level groups. We herein describe two new species, Megophrys fansipanensis sp. nov. and Megophrys hoanglienensis sp. nov. Both new species are range restricted and likely to be highly threatened by habitat degradation. These discoveries highlight the importance of the Hoang Lien Range for Vietnam’s amphibian diversity.